Association of exercise and ADHD symptoms: Analysis within an adult general population sample - RORY TUCKER (PLOS ONE, 2025)
Given the limitations associated with existing treatments for Attention Deficit/Hyperactive disorder (ADHD), Physical Activity (PA) has been considered as an adjunct therapeutic option. Previous research has generally found that PA reduces ADHD symptoms in children. However, much less research has explored the same effects in adults, and especially females, with ADHD. This cross-sectional study investigated the relationship between PA and ADHD in adults, and whether any relationship was moderated by proxy diagnostic ADHD group, as well as exploring the roles of motivation and forms of exercise. 268 participants completed an online survey measuring proxy ADHD diagnosis; ADHD symptomatology; PA level; forms of exercise performed, and motivation for exercise. In contrast to previous research performed with child participants (which frequently found significant negative correlations), there was no significant relationship between PA level and total ADHD symptomatology in adults, but there was a significant negative correlation between PA level and inattentive ADHD symptomatology. The strength of relationship between PA level and ADHD symptomatology did not differ based on ADHD proxy diagnostic grouping; PA level based on motivation type; or PA level based on total forms of exercise performed. However, it may be that clear relationships between PA and ADHD symptomatology are not easily identifiable in adult populations when only broad, nonspecific variables/measures are used (e.g., only measuring ADHD symptoms as a continuous total score, rather than considering inattentive/hyperactive symptoms separately). Therefore, greater differentiation between ADHD symptoms and subject characteristics (such as gender) might be required to better establish potential relationships and effects in this area, and better inform any potential PA based treatments.